DETERMINAN MINAT INVESTASI DI PASAR MODAL : (STUDI PADA MASYARAKAT KECAMATAN NGEMPLAK, KABUPATEN SLEMAN, DIY) - Suryawan, Teguh; Pratama Indrianto, Anggraeni (FEB Universitas Sam Ratulangi Manado, 2024)
This study aims to explore the factors influencing individuals' interest in investing in the capital market, focusing on variables such as Expected Return, Self Efficacy, Perceived Risk, Subjective Norms, Perceived Behavior Control, and Investment Attitudes. Data were collected through a survey of respondents who are members of the general public in Ngemplak District, Sleman Regency, DIY. Data analysis was conducted using relevant statistical methods with the assistance of SPSS 25 software. The main findings indicate that all variables examined have a significant influence on individuals' interest in investing in the capital market. These results underscore the importance of considering psychological aspects and perceptions in planning strategies to increase public participation in investment. The implications of this research highlight the necessity of developing holistic, data-driven approaches to enhance financial literacy and community involvement in the capital market.